Role of Burkholderia pseudomallei exotoxin in the pathogenesis of melioidosis using mice model - Aliyu, Rabiu Muhammad (2016)
Burkholderia pseudomallei is a gram-negative bacterium and a causative agent of melioidosis, a serious often fatal multisystem disease of man and animals. In Malaysia, B. pseudomallei have been isolated from different subjects in the states of Pahang, Johor, Kuala Lumpur and Kedah. Strains of B. pseudomallei were known to secrete a range of extracellular enzymes (exotoxins) with different lethal activities such as proteolytic, lipolytic, haemolytic activities. However, little study has been conducted on the characteristic of exotoxins from Malaysian isolates. Similarly, there is scarce of information related to the role of the local B. pseudomallei isolates and its associated exotoxins in the pathogenesis of melioidosis. This study is aimed to determine the molecular characteristics of B. pseudomallei as well as to study the role of its exotoxin in the pathogenesis of melioidosis. Three B. pseudomallei isolates designated UPM/20 12110 17, UPMl2013/006 and UPM/2013/577 strains used in this study were obtained from cases of animal melioidosis presented to Universiti Veterinary Hospital (UVH), Universiti Putra Malaysia (UPM). The isolates were reconfirmed phenotypically and biochemically followed by confirmation using 16S rRNA sequencing. Sequencing and phylogenetic analysis of the isolates showed that they were closely related to B. pseudomallei K96243 and 1026b strains from Thailand as well as B. pseudomallei MSHR2543 strain from Australia. B. pseudomallei K96243, 1026b and MSHR2543 strains were among highly virulent B. pseudomallei strains known globally and most frequently reported from humans, indicating possible zoonotic potentials of these local B. pseudomallei strains. This study suggested the existence of fatal animal melioidosis caused by these B. pseudomallei strains. Analysis of their extracellular virulence genes (exotoxins) revealed the presence of three genes encoding for phospholipase C and a gene encoding for a protease. Further characterization of the isolated extracellular proteins (exotoxin) by SDS-PAGE analysis indicated the presence of phospholipase C enzyme with a molecular weight of 77 kDa. Following protein characterization, an in \'i\'O assay using BALB/c mice was carried out to evaluate the toxigenicity of the extracellular protein isolated. A total of 130 BALBlc mice used in this study were divided into 5 treatment groups: control (Cx) (n =10), live B. pseudomallei (Bp) (n =30); live B. thailandensis (Bt) (n =30); B. pseudomallei exotoxin (E) (n =30) and B. thailandensis supplemented with B. pseudomallei exotoxin (Bt + E) (n =30). Live bacteria groups were inoculated with 5 x 104,5 X 103 and 5 x 102 Colony-forming units (CFU) of either B. pseudomallei or B. thailandensis respectively. The exotoxin groups were inoculated with 50.0 ug; 25.0 ug and 12.5 !lg exotoxin either alone or mixed with 5 x 104 , 5 X 103 and 5 x 102 CFU of B. thailandensis respectively. Negative control groups (Cx) received sterile PBS (pI! 7.4) only. Clinical signs such as loss of body weight, change in appearance, behaviour and activity of the animal were monitored and recorded for 14 days. Lethal dose-50 (LDso) and survival analysis were calculated. Organ bacterial burden, haematological, gross and histopathological analyses were conducted. There was significant (p<0.05) dose-dependent increase in the susceptibility of the BALB/c mice treated with the live bacteria (group Bp and Bt) following IN inoculation as compared to SC inoculation. This contrast with the observation in the groups of mice inoculated with exotoxins (E and Bt + E) in which those in the SC groups showed more susceptibility than IN inoculated groups. The most striking finding in this study was the enhancing of B. thailandensis pathogenicity following its supplementation with B. pseudomallei exotoxin isolated in this study. This was due to the fact that, although group Bt showed significant gross, histopathology, haematology body weight changes over time when compared to the uninfected control, mortality was not recorded, however, in group Bt + E, there was significant (p<0.05) morbidity and mortality when compared to the Bt and Cx groups. When these are combined with the findings of this study that showed the abundance of the exotoxin genes in B. pseudomallei while absent in B. thailandensis, suggested that the B. pseudomallei extracellular products (exotoxins) are necessary for virulence and pathogenicity observed in this bacterium. In conclusion, this study showed that the isolates contained exotoxin (phospholipase C) encoded by Plc-l , Plc-2 and plc-3 genes. The exotoxin plays an important role in the pathogenesis of melioidosis as it resulted in morbidity and mortality in mice model. Further studies should focus on cloning of this exotoxin in order to obtain the purest protein to be used in developing toxin (Toxoid) candidate for the use in countermeasures of melioidosis. Similarly, the exotoxin shall be evaluated in other models such as Nematodes models and in vitro cell lines in order to gain a wider understanding of its toxicity.